Shylock is my name : the merchant of Venice retold - Jacobson, Howard (Hogarth Shakespeare., 2016)
In a modern re-imagining of Shakespeare's Shylock--Simon Strulovitch, riddled with grief after the death of his wife, struggles with his daughter Beatrice's betrayal of family and his daughter Jessica's rejection of her Jewish roots.